Sambiloto (Andrographis paniculata) Extract Improves the Performance of Animal Model Infected with Escherichia coli - Sri Hidanah1 , Emy Koestanti Sabdoningrum1 , Mohammad Anam Al Arif1 , Arif Nur Muhammad Ansori2 , Ta (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aims to understand the effect of natural antibiotics from sambiloto (Andrographis paniculata)extract to laying hens infected with Avian Pathogenic Escherichia coli (APEC). The activation test ofsambiloto was performed by using a dilution method included a minimum inhibitory concentration (MIC)and a minimum bactericidal concentration (MBC). Laying hens were distributed into five groups: normalgroup, APEC group with no treatment, and APEC group given 10%, 20%, 30% sambiloto extract for twoweeks. The data were analyzed using ANOVA and continued with the F test. Based on the results, the 30%extract has improved the hen day production (HDP) of laying hens infected with APEC.